Predicting Green Purchase Intention via Green Brand Trust, Image, and Perceived Value: An Empirical Study of Kopi Tuku Consumers in Surabaya - Randy Oktavianus Gunawan; Dewi Deniaty Sholihah (Research Synergy Foundation, 2026)
Despite corporate sustainability efforts, a research gap remains regarding how green attributes translate into buying intent within highly skeptical youth cohorts in localized emerging markets. This cross-sectional study evaluates the associative relationships among green brand image, green perceived value, green brand trust, and green purchase intention among 160 Generation Z consumers of Kopi Tuku in Surabaya, Indonesia. Pathways were analyzed using PLS-SEM with a bootstrapping procedure of 5,000 subsamples and bias-corrected confidence intervals. The findings reveal that green brand image exhibits a non-significant direct association with green purchase intention, yet relies on the full mediation of green brand trust. Conversely, green perceived value reflects a significant direct association with purchase intention, while concurrently displaying a significant indirect relationship through the partial mediation of green brand trust. Both variables serve as vital psychological anchors within this sample. This investigation provides a measured empirical contribution to green marketing literature by demonstrating that a sustainable image is insufficient to account for behavioral intentions unless structurally converted into verified trust and backed by perceived environmental utilities, offering targeted insights for regional coffee businesses navigating urban youth markets.